Toxicity of magnetic chitosan micro and nanoparticles as carriers for biologically active substances - Heržič, Katja (Acta chimica slovenica, 2014)
Nanoparticles of inorganic magnetic core surrounded by layers of functional coatings are potential representatives of nanostructures for immobilization of bio-substances. Magnetic nanoparticles (MNPs) are often bound in aggregates due to a strong magnetic dipole, which has a lot of advantages, such as large surface area for binding biologically active substances. Chitosan is a polysaccharide polymer that is non-toxic, hydrophilic, biocompatible and has hydroxy and amino groups in its structure. Because of these chemical and biological properties it is a desirable bio-product for immobilization of enzymes and for binding of other biologically active substances. Magnetic micro and nanoparticles were synthesized with chitosan by three different methods; microemulsion process, suspension cross-linking technique and covalent binding of chitosan. Toxic effect of the prepared magnetic particles was determined as well and was examined on five different bacterial cultures; Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis and Klebsiella pneumoniae. At concentrations of 10-30 mg of magnetic particles per 0.5 McFarland Standard solution of E. coli and per 400 CFU of S. aureus, P. aeruginosa, E. faecalis in K. pneumonia, no inhibition on the chosen bacterial cultures was detected.
Keywords: biološko aktivne snovi; biosubstance; hitozan; magnetni mikrodelci; magnetni nanodelci; toksikološki testi